Effectiveness of an Educational Program on Female Students’ Practices toward Premenstrual Syndrome at Secondary Schools in Third Al- Rusafa Education Directorate - Sarab Mansoor Mahdi,; Suhad H. Khairi, (Iraqi National Journal of Nursing Specialties, 2022)
Objective: Determination the effectiveness of educational program on female students’ practices toward premenstrual.Methodology: A quasi-experimental design study was conducted involving (140) student purposely in four secondary schools at Al-sadder city (70) student for study group and (70) for control group. The prevalence of PMS selected through American College of Obstetricians and Gynecologists (ACOG) (2015) criteria to select PMS students before program. The education program were set in four steps, the first step (pre-test) is to assess the practices, before the implementation of the program, the second step is implementing the program, following two steps post-test  I and II between each test two weeks. Validity is determined through a panel of experts, and the reliability of the questionnaire is determined through a pilot study of ten students. Data analyzed through descriptive inferential statistics. Results: The study indicates that the number of study sample that reported having premenstrual syndrome was (140). There were significant differences at (P- value≤ 0.01) between pretest, posttest I and posttest II. A significant difference results were found between the first test before the implementation of the program and the two tests after implementation the program, compared to the control group.Recommendations: The study recommended that early education courses in primary school regarding menstruation, premenstrual syndrome, and self-care measures